Pengelolaan Sertifikasi Tim Pekerjaan dalam Keadaan Bertegangan (PDKB) PT Perusahaan Listrik Negara (Persero) Unit Induk Distribusi Banten - ; Masutiah Susilowati (Syntax Idea)
This research examines the management of certification for Workers in Tense Conditions (PDKB) teams at PT Perusahaan Listrik Negara (Persero) Unit Induk Distribusi Banten. A qualitative method with a descriptive approach was used to understand this phenomenon in its natural context. Data were collected through in-depth interviews, field observations, and document analysis. The results of the analysis revealed a placement strategy for employees based on a merit system. This study emphasizes the importance of meaning over generalization. The findings provide deep insights into the management of PDKB certification at PT Perusahaan Listrik Negara (Persero) Unit Induk Distribusi Banten. This research makes a significant contribution to improving the certification management process and ensuring compliance with applicable regulations and laws.